A European Tax on Foreign Exchange Transactions? - Sandor Richter (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2007)
First paragraph: The financing of the redistribution of resources across member states of the European Union (EU), the EU's »own resources«, currently consists of three main components: customs duties collected at the common external border of the customs union, part of the value added tax (VAT) revenues in the individual member states calculated by statistical methods (VAT-based own resources) and, as the biggest part, the component proportional with the member states' gross national income (GNI) (GNI-based own resources) calculated by a unified rate. This system lends decisive leverage to the national treasuries in negotiations about the size and, to a lesser extent, the ways of the allocation of funds earmarked for cross member state redistribution by the EU. The periodically returning debates and the disappointing bargaining about the financial perspectives for 2007 to 2013 have led to the proposal for a comprehensive review of the EU budget in 2008 /2009. The forthcoming review provides an opportunity for initiating fundamental reforms which may take two diff erent courses. The first one is the extension of the GNI-based component of the current system, with member state contributions reflecting as closely as possible the differences in the individual member states' economic strength. This would be a transparent, simple, efficient and fair system in terms of burden sharing at member state level. The alternative course of reform relies on the principle that the EU should increasingly become a »Union of the citizens«, therefore the »own resources« should be collected through the introduction of a European tax. In the past decade several options for a European tax were discussed: income taxes (personal income tax, corporate income tax, withholding tax on interest income, and transfer of seigniorage revenue); taxes on real transactions (genuine VAT, taxation of energy, communication taxation, climate charge on aviation, and excise duties on tobacco and alcohol); and finally a tax on financial transactions (tax on stock exchange transactions in shares and bonds). This latter group has recently been extended by proposals for a tax on foreign exchange transactions. This paper addresses the pros and cons of a European tax on foreign exchange transactions.
Keywords: 330